Karakteristik Mutu Minyak Pala Berdasarkan Peralatan Distilasi Drum Bekas dan Distilasi Stainless (Studi Kasus di Kabupaten Aceh Selatan) - Mustafril Mustafril (Department of Agricultural Engineering, Syiah Kuala University, 2017)
Quality Characteristics of Nutmeg Oil Between Used Barrels Distillation and Stainless Distillation (A Case Study in Aceh Selatan Regency)ABSTRACT. The Province of Aceh is the center of nutmeg oil production in Indonesia, which is about 70%-75% of the nutmeg oil production in Indonesia, is produced in the districts of South Aceh and Southwest Aceh. The rest is coming from the provinces of West Sumatra and West Java. Meanwhile, the nutmeg harvested in Maluku, North Maluku, North Sulawesi, and West Papua is not processed for its essential oil, but merely exported as spices. It is estimated that in 2017 the production of nutmeg oil will reach about 350-400 tones. The government has put a standard for nutmeg oil based on SNI 06-2388-2006. Therefore, taking this standard as consideration, a study on the characteristics of nutmeg oil quality in South Aceh was carried with 14 distillers as the sample. The tested nutmeg oil was taken from the distillers, both stainless distillation drum and used drum. The characteristics of nutmeg oil coming out of the used drum is from colorless to pale yellowish one, has nutmeg scent, specific gravity: 0,884 - 0,960, rafractive index: 1,481-1,500, optical rotation: (+)6,20o - (+)19,30o and rest of evaporation is between 5,70% - 28,15%. On the other hand, the characteristic of nutmeg oil taking from stainless distiller is colorless, has nutmeg scent, specific gravity: 0,861 - 0,892 refractive index: 1,472 - 1,484, optical rotation: (+)10,83o- (+)18,00o, and rest of evaporation is 0,50% - 4,80%. Most of nutmeg oil processed by used drum did not meet the SNI standard, whereas few of nutmeg oil distilled in stainless and semi stainless drum has met the SNI standard of nutmeg oil.Correlation of specific gravity and refraction index of nutmeg oil for stainless distillation is refraction index (Y) = 0,3151X + 1,2014, where R2 = 0,8403; whereas for used barrels distillation is refraction index (Y) = 0,28X + 1,2334, where R2 = 0,9637.Correlation of Optical Rotation for stainless distillation is Optical Rotation (Y) = -223,02X + 209,81, where R2 = 0,9645;conversely, forused barrels distillation Optical Rotation (Y) = -155,01X + 156,2, where R2 = 0,9348.Correlation of refraction index with Optical Rotation for nutmeg oil distilled with stainless distillation is Optical Rotation (Y) = -610,36X + 915,96, where R2 = 0,8536; contrarily for distillation with used barrels Optical Rotation (Y) = -545,71X + 827,26, where R2 = 0,9427.